Penapisan Aktivitas dan Senyawa Antidiabetes Ekstrak Air Daun Dandang Gendis (Clinacanthus nutans) - Nurulita, Yuana; Dhanutirto, Haryanto; Soemardji, Andreanus A. (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
An investigation of the antidiabetic activity of Aqueous Extract and its fractions from a different polarity solvent:ethanol, ethyl acetate, and n-hexane of Dandang Gendis Leaves (Clinacanthus nutans Lindau) on Mile SwissWebster Mice has been carried out. The effect of aqueous extract of dose of 50, 100, and 150 mg/kg BW wastested on glucose serum level of alloxan induced that mice. Its fractions were tested by glucose tolerance method.Aqueous extract (150 mg/kg BW) significantly decreased blood glucose serum level (pd”0,05) that had the sameeffect as oral glibenclamide (0,65 mg/kg BW) administrated once a day for 9 days. Aqueous extract that wasfractionated has 5 fraction. Fraction of ethanol extract that was insoluble in ethyl acetate at a dose of 100 mg/kgBW was the most active fraction, that significantly (p<0,05) decreased blood glucose serum level of mice atglucose tolerance method of 18,4% in 3 hours after 2 g/kg BW of glucose administration. Thin layer chromatography(TLC) of that fraction ethanol 95%-chloroform 9:2 as eluent gave 5 spots under ultraviolet ray and showed spesificcompounds by qualitative test. Spot 1 (steroid) gave Rf 0,14; spot 2 and spot 3 that gave Rf 0,53 and 0, 67 wereflavonoid, spot 4 (triterpenoid) gave Rf 0,77; and spot 5 (chlorophyll) gave Rf 0,89. This research show that this plantcan used for hipoglicemic traditional medicine.